Parental Knowledge and Attitudes Towards Childhood Immunization - Čiutienė, Elena (Slauga. Mokslas ir praktika, 2022)
Currently, there is a significant outbreak of immunization worldwide. However, coverage of vaccination of children is declining, even in developed countries. As studies show, educational background of parents, their place of residence (city or village), financial situation and age may have an effect over immunization. In addition, according to researchers, the number of unvaccinated children in private educational institutions may be higher than in public ones, and factors related to the availability of vaccines may have an effect over vaccination coverage. It is therefore important to analyse the situation in Lithuania and especially in regions where coverage of immunization is declining. 387 respondents from 10 pre-school institutions took part in the study. Haemophilus influenzae type b (Hib) Vaccine was the least known to the participants in the study. Meanwhile, vaccines against pertussis, diphtheria, tetanus, and measles, mumps, rubella are the most known. The respondents are also the least aware of the use of vaccines to prevent mumps and Haemophilus influenzae type B infection. The majority of respondents said they do not know the vaccination schedule, and half of those respondents who said they know it could not identify a single time of vaccination. Most of the parents who participated in the study yet choose to vaccinate their children with all state-reimbursed vaccines, and fear of side effects is identified as the most common reason for the decision not to vaccinate children. The study revealed an important link between the refusal from being vaccinated with state-reimbursed vaccines and attendance of private kindergarten. Although parents have little knowledge about immunization, their attitude, however, remains favourable. The respondents have a welcoming opinion about the situation regarding the availability of immunization services, and this should not affect the choice to refuse from immunization. However, the gender, educational background of the respondents and the monthly income received by the family had a statistically significant effect on the knowledge of the persons who participated in the study about vaccination. And persons who refuse to vaccinate their children with state-reimbursed vaccines have poorer knowledge of and are characterized by inferior attitude towards immunization, and, in addition, they have worse opinion about availability of immunization services.